Recurrent stroke after cervical artery dissection. Issue 8 (3rd August 2010) - Weimar, Christian; Kraywinkel, Klaus; Hagemeister, Christoph; Haaß, Anton; Katsarava, Zaza; Brunner, Freimuth; Haverkamp, Christian; Schmid, Elisabeth; Diener, Hans-Christoph; ,
Abstract : Objective: Cervical artery dissection (CAD) accounts for 10–20% of all strokes in young adults, but no randomised controlled trial has investigated the best secondary prevention after ischaemic stroke or transient ischaemic attack (TIA). Because only small numbers of patient with CAD have been prospectively documented and followed up, the authors aimed to investigate the prognosis under various prevention regimens. Methods: 30 German departments of neurology with acute stroke units prospectively documented 250 patients with acute ischaemic stroke or TIA due to CAD. A central follow-up (median 31 months) assessed recurrent stroke, recurrent CAD and death in 198 patients. Results: CAD was found more often in the carotid arteries (52.0%) than in the vertebral arteries (46.8%). Thirteen patients (5.2%, CI 3.1% to 8.6%) suffered a recurrent stroke during the acute hospital stay. The rate of recurrent CAD during the first year was 1.7% (95% CI 0.3% to 3.6%). The cumulative recurrent stroke rate during the first year was 10.7% (95% CI 6.5% to 14.9%) and 14.0% (95% CI 8.9% to 19.1%) over 3 years. After discharge, the rate of recurrent stroke up to 6 months in patients treated with anticoagulants was 2.0% (95% CI 0.6% to 7.1%) and in those treated with antiplatelets 16.7% (95% CI 5.8% to 39.2%), which was statistically significant (HR 0.11; CI 0.02 to 0.69, p=0.02). Conclusions: This observational study confirms a high risk of early recurrent stroke following acute IS or TIA due to CAD. Whether anticoagulation provides any benefit over antiplatelets needs to be investigated in a randomised controlled trial.